Typhoid fever, complicated by myocarditis, in a traveller returning to the UK. (15th February 2013) - Shah, Shreena; Dubrey, Simon William
Abstract : A 25-year-old male returning traveller presented with sudden onset chest pain. An ECG showed infero-lateral ischaemic changes, with an elevated troponin and inflammatory markers. An echocardiogram showed a normal size left ventricle, dynamic systolic function, structurally normal valves and no regional wall motion abnormality. Angiography revealed normal coronary arteries. A diagnosis of myocarditis was made. Five days later, he developed a significant pyrexia and diarrhoea. Salmonella typhi was isolated from blood cultures. The fever and symptoms resolved after 2 weeks of an intravenous third generation cephalosporin and the patient was discharged.